2016
DOI: 10.18632/oncotarget.12587
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of EGFR mutation in patients with non-small cell lung cancer: a systematic review and meta-analysis

Abstract: ObjectivesEstimate the epidermal growth factor receptor (EGFR) mutation prevalence in all non-small cell lung cancer (NSCLC) patients and patient subgroups.ResultsA total of 456 studies were included, reporting 30,466 patients with EGFR mutation among 115,815 NSCLC patients. The overall pooled prevalence for EGFR mutations was 32.3% (95% CI 30.9% to 33.7%), ranging from 38.4% (95% CI: 36.5% to 40.3%) in China to 14.1% (95% CI: 12.7% to 15.5%) in Europe. The pooled prevalence of EGFR mutation was higher in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
416
4
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(472 citation statements)
references
References 41 publications
38
416
4
14
Order By: Relevance
“…Examining its mutation is not only important to understand tumorigenicity element in NSCLC but also crucial to patient treatment with TKI-targeting therapy. Even mostly consistent with previous reports, 3,19 our data still provides some important information in this dominated abnormality of LAC. Our results showed that L858R in exon 21 (51/93, 54.83%) and exon 19 deletions (38/93, 40.86%) are the two major defects which account for more than 95% EGFR mutations in LAC.…”
Section: Discussionsupporting
confidence: 93%
“…Examining its mutation is not only important to understand tumorigenicity element in NSCLC but also crucial to patient treatment with TKI-targeting therapy. Even mostly consistent with previous reports, 3,19 our data still provides some important information in this dominated abnormality of LAC. Our results showed that L858R in exon 21 (51/93, 54.83%) and exon 19 deletions (38/93, 40.86%) are the two major defects which account for more than 95% EGFR mutations in LAC.…”
Section: Discussionsupporting
confidence: 93%
“…Non-small cell lung cancer (NSCLC) accounts for 85% of all lung cancers and the cornerstone of management for advanced stage disease has traditionally been cytotoxic chemotherapy, albeit with low response rates (20% to 25%) and overall survival (OS) of 10-12 months (2,3). The discovery of driver mutations in the epidermal growth factor receptor (EGFR) gene in a subset of patients with NSCLC and the development of oral tyrosine kinase inhibitors (TKIs) targeting these mutant receptors has remarkably changed the therapeutic landscape in advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…It has led to improved progression free survival as well as quality of life in this patient population (4). The prevalence of sensitizing EGFR mutation ranges from 14% to 38% in patients with NSCLC depending on geographic location and ethnicity (3). These mutations are more commonly present in women, nonsmokers and Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…While the EGFR is commonly upregulated in many cancers such as in non‐small‐cell lung cancer (NSCLC), metastatic colorectal cancer, glioblastoma, head and neck cancer, pancreatic cancer and breast cancer, erlotinib is currently approved to be used in metastatic non‐small‐cell lung cancer and metastatic pancreatic cancer . In fact, since the oncogenic activation of the EGFR gene is implicated as a driver mechanism in 14.1%‐38.4% of NSCLC tumours, EGFR TKIs have become the standard‐of‐care in the treatment of stage IV NSCLC …”
Section: What Is Known and Objectivementioning
confidence: 99%